دراسة تأثير بعض قواعد شف على فعالية أنزيم الفوسفاتيز القاعدي في مرضى سرطان العظام في الرجال (مجلة ديالى للبحوث الانسانية, 2022)
تمت دراسة فعالية أنزيم الفوسفاتيز القاعدي في أمصال الدم لـ (30 ) عينة للرجال مصابين بسرطان العظام من مستشفى مدينة الطب /بغداد وقد لوحظ زيادة الفعالية الأنزيمية الكلية في الحالات المرضية حيث وصلت الى( 41.53 K.A.U./100ml ) مقارنة بالقيمة الطبيعية لفعالية أنزيم الفوسفاتيز القاعدي في مصل دم البالغين الأصحاء التي تكون ضمن المدى       (3-13 K.A.U./100ml). تم دراسة تأثير المركبين 7-nitro isatindine nicotinoyl hydrazide ,    Isatindine nicotinoyl hydrazide  على فعالية أنزيم الفوسفاتيز القاعدي في مصل الدم من خلال تحضير سلسلة من التراكيز (2*10-8, 2* 10-7, 2* 10-6,2* 10-5)                            M لكل من المركببين من المحلول القياسي (stock solution) بتركيز (M 10-4) لكل منهما وقد استخدم DMSO كمذيب ولغرض التخفيف، بعد أن تم قياس تأثير DMSO التثبيطي على أنزيم الفوسفاتيز القاعدي في مصل الدم والذي بلغ (2.76±0.5%)ومن خلال إجراء الفحوصات وجد أن المركبين يمكن اعتبارهما مثبطات جيدة بالتراكيز المستخدمة، حيث بلغ مدى النسبة المئوية للتثبيط (50-65%) وذلك باستخدام التركيزالأعلى للمثبطات (M 2*10-5) في مصل دم للمصابين .AbstractThe level of Alkaline phosphatase was studied in the blood serum of (30) sample of men with bone cancer hospital in the town of Medicine / Baghdad has been observed to increase the overall effectiveness enzyme in patients with an average of (41.53 KAU/100ml) compared to the value of the effectiveness of the natural enzyme in theAlkaline phosphatase activity in sera of normal adults was in the ranges  3-13 K.A.U./100ml .                       The effect of compounds 7-nitro isatindine nicotinoyl hydrazide             Isatindine nicotinoyl hydrazide. the effectiveness of enzyme (ALP)  of with concentration(2*10-8, 2* 10-7, 2* 10-6,2* 10-5) of tow compounds in blood sera of stock solution concentration (M 10-4) and DMSO was used as solvent and diluents , The inhibitory effect of DMSO on Alkaline phosphatase in blood sera was(2.76±0.5%) the two compounds have a good inhibitory in this concentration theRatio was (50-65) with the high concentration of inhibitor was (M2*10-5)in sera of patients.